Cognition blindness and cognitive gadgets - Heyes, C (Cambridge University Press, 2019)
Responding to commentaries from psychologists, neuroscientists, philosophers, and anthropologists, I clarify a central purpose of Cognitive Gadgets – to overcome “cognition blindness” in research on human evolution. I defend this purpose against Brunerian, extended mind, and niche construction critiques of computationalism – that is, views prioritising meaning over information, or asserting that behaviour and objects can be intrinsic parts of a thinking process. I argue that empirical evidence from cognitive science is needed to locate distinctively human cognitive mechanisms on the continuum between gadgets and instincts. Focussing on that requirement, I also address specific challenges, and applaud extensions and refinements, of the evidence surveyed in my book. It has been said that “a writer's idea of sound criticism is ten thousand words of closely reasoned adulation.” I cannot disagree with this untraceable wag, but the 30 commentators on Cognitive Gadgets provided some 30,000 words of criticism that are of much greater scientific value than adulation. I am grateful to them all. The response that follows is V-shaped. It starts with the broadest conceptual and methodological issues and funnels down to matters arising from specific empirical studies.